Trans-radial cerebral angiography-safety, efficacy and patient comfort: review of literature - Dalai, Sibasankar; Behera, Hemant K.; Datla, Aravind V.; Jalamanchili, Prithvi (International Journal of Advances in Medicine, 2022)
A diagnostic cerebral angiography is a vital tool in the planning and management of various cerebrovascular conditions. Newer angiographic modalities, such as digital subtraction angiography offers dynamic imaging of the cerebral blood flow and is the preferred diagnostic modality of choice when a subsequent intervention is contemplated. Traditionally, the transfemoral route at the groin was used as the site for vascular access. However, landmark randomised controlled trials in the field of interventional cardiology have demonstrated the safety, efficacy and patient comfort attained by employing a trans-radial access for angiography and interventions. This has spawned numerous studies which were directed explicitly towards cerebral angiography and neuro-intervention. We present this review of literature to consolidate the current practices and to encourage the neuro-interventionalists to shift to a radial first approach.